Post-launch calibration of satellite sensors : proceedings of the International Workshop on Radiometric and Geometric Calibration, December 2003, Mississippi, USA /: proceedings of the International Workshop on Radiometric and Geometric Calibration, December 2003, Mississippi, USA. ([2004]) - Unknown
No abstract available